Interpersonal Communication Dynamics of Universitas Terbuka Students in the Social Media Era - rohimah, Afifatur; Aprilia, Khania (Journal Commedies, 2025)
This study examines the dynamics of interpersonal communication among Universitas Terbuka students in the era of social media, focusing on the use of WhatsApp as the primary medium of interaction. As a distance-learning institution, Universitas Terbuka relies on social media to bridge the physical and geographical gaps between students, making it an essential platform for fostering communication. Employing a qualitative case study approach, the research involved in-depth interviews with active students from various academic disciplines. Findings indicate that WhatsApp plays a central role in enabling fast, flexible, and efficient communication in both academic and social contexts. Nevertheless, such communication also faces challenges, including miscommunication and blurred boundaries between private and public spheres. Despite these challenges, students tend to build social bonds and collaborate effectively through WhatsApp-based communication.